2022
DOI: 10.1017/s096719942200051x
|View full text |Cite
|
Sign up to set email alerts
|

Micro-TESE surgery combined with ICSI regimen in the treatment of non-obstructive azoospermia patients and its effect analysis

Abstract: Summary This study aimed to analyze the clinical effects of microdissection testicular sperm extraction (micro-TESE) surgery combined with an intracytoplasmic sperm injection (ICSI) regimen in the treatment of non-obstructive azoospermia (NOA) patients with different etiologies. In total, 128 NOA patients participated in this study, in which they received infertility treatment by micro-TESE surgery combined with an ICSI regimen, and all patients were divided into three groups [the Klinefelter syndrome (KS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In our study and its groups, this rate is lower than what is reported in the literature. Although the number of patients is small and there is only one patient in the patient group with solitary testis (total 13 patients), our SRR in this patient group is within the range reported in the literature [15].…”
Section: Discussionsupporting
confidence: 72%
“…In our study and its groups, this rate is lower than what is reported in the literature. Although the number of patients is small and there is only one patient in the patient group with solitary testis (total 13 patients), our SRR in this patient group is within the range reported in the literature [15].…”
Section: Discussionsupporting
confidence: 72%